1998
DOI: 10.1042/bj3301235
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of human fibroblast-derived mitogenic factors for human melanocytes

Abstract: To clarify the paracrine linkage between human fibroblasts and melanocytes in cutaneous pigmentation, we studied the effects of human fibroblast-derived factors on the proliferation of human melanocytes. In medium conditioned for 4 days with human fibroblast culture, factors were produced that markedly stimulated DNA synthesis of human melanocytes. The stimulatory effect was higher in medium conditioned with fibroblasts from aged skin than in medium conditioned with fibroblasts from young skin, and was interru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 13 publications
1
93
0
1
Order By: Relevance
“…The formation of IP 3 following stimulation is a hallmark for evaluation of PKC activation because IP 3 and the protein kinase C activator, diacylglycerol, are simultaneously generated at an equimolar ratios. The time course of formation of IP 3 following SCF and ET-1 treatment revealed that there is no difference in The mechanism of tyrosine kinase receptor-stimulated mitogenic signaling involves the formation between complexes of the guanine nucleotide exchange protein SOS, and the SH2 and SH3 domain-containing adaptor protein Grb2 with another tyrosine-phosphorylated adaptor protein Shc (21-23). Recent studies have shown that some G protein-coupled receptors utilize the same effectors as the tyrosine kinase receptor pathway (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of IP 3 following stimulation is a hallmark for evaluation of PKC activation because IP 3 and the protein kinase C activator, diacylglycerol, are simultaneously generated at an equimolar ratios. The time course of formation of IP 3 following SCF and ET-1 treatment revealed that there is no difference in The mechanism of tyrosine kinase receptor-stimulated mitogenic signaling involves the formation between complexes of the guanine nucleotide exchange protein SOS, and the SH2 and SH3 domain-containing adaptor protein Grb2 with another tyrosine-phosphorylated adaptor protein Shc (21-23). Recent studies have shown that some G protein-coupled receptors utilize the same effectors as the tyrosine kinase receptor pathway (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The radioactivity on the filter was directly measured using MATRIX 96 (Packard Bioscience Co.). 3 . Extraction of Cellular Proteins-Cells were incubated with ET-1 and/or SCF in 60-mm diameter culture dishes, then solubilized in 500 l of ice-cold RIPA (radioimmunoprecipitation) buffer containing 50 mM Tris-HCl (pH 7.5), 150 mM NaCl, 1% Nonidet P-40, 0.25% Na deoxycholate, 1 mM EDTA, 50 mM NaF, 1 mM sodium orthovanadate, 50 mM phenylmethylsulfonyl fluoride, and 1 mg/ml aprotinin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 GM-CSF is a potent autocrine mitogen for KCs. 77,78 GM-CSF activity results in faster wound closure, but it has not been established whether this effect is due to increased KC proliferation resulting from increased KC production of the mitogenic factors IL-6 and interferon-c, increased migration of KCs into the wound bed, or a combination of the two. 79,80 Clinically, the application of recombinant GM-CSF has been shown to be efficacious for the treatment of chronic wounds and burns but has no effect on wound healing in healthy individuals; these effects are most likely mediated through increased recruitment of macrophages and neutrophils and increased vascularization at the wound site rather than via a direct effect on KC migration.…”
Section: 32mentioning
confidence: 99%
“…A few of these cytokines are known mitogens for human melanocytes, including basic fibroblast growth factor, SCF, granulocyte-macrophage colony-stimulating factor, hepatocyte growth factor, and ET-1. [42][43][44][45][46] Several cytokines, such as IL-1␣ and TNF-␣, significantly increase the expression of SCF protein by cultured human keratinocytes. 5 Accordingly, MIF may induce PAR-2 to mediate cutaneous pigmentation by increasing both the uptake of melanosomes by keratinocytes and the release of SCF, which stimulates melanogenesis.…”
Section: Discussionmentioning
confidence: 99%